2019
DOI: 10.1002/ep.13359
|View full text |Cite
|
Sign up to set email alerts
|

Steady state operation exergy‐based optimization for solar thermal collectors

Abstract: In this investigation, exergy-based optimization was carried out on two configurations of solar thermal collectors. A set of control sensors were utilized to control the performance of the system and monitor the design variables, that is, inlet and outlet temperature of the solar fluid, ambient temperature, incident solar flux, and required mechanical and electrical work in the system. The fluid temperature was considered to vary in the range of 120-180 C with respect to technical and economic considerations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The solar energy intercepted by the collector is calculated from Q˙collector=italicAG, where A and G are solar collector area and solar radiation intensity per unit of collector area (W/m 2 ), respectively. The energy absorbed by the collector is calculated using Q˙i=ζ0.25emQ˙collector, where ζ is the solar collector efficiency calculated by ζ=ζoa1TGa2T2G, where the constants ζ o , a 1 , and a 2 are given by the CPC manufacturer. ∆T is the temperature difference between the hot engine cylinder and ambient temperature.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The solar energy intercepted by the collector is calculated from Q˙collector=italicAG, where A and G are solar collector area and solar radiation intensity per unit of collector area (W/m 2 ), respectively. The energy absorbed by the collector is calculated using Q˙i=ζ0.25emQ˙collector, where ζ is the solar collector efficiency calculated by ζ=ζoa1TGa2T2G, where the constants ζ o , a 1 , and a 2 are given by the CPC manufacturer. ∆T is the temperature difference between the hot engine cylinder and ambient temperature.…”
Section: Methodsmentioning
confidence: 92%
“…The CPC can achieve moderate temperatures up to 200°C and presents a good compromise between simplicity and thermal performance . Grosu et al showed by exergy analysis that CPC is a high‐performance collector and can technically and economically achieve temperatures as high as 180°C. However, to the best of the authors knowledge, no Stirling engine has been directly coupled to the CPC.…”
Section: Introductionmentioning
confidence: 99%
“…The primary use of a solar collector is the collection of solar energy and the transfer of heat to a fluid. This heat can then be removed from the fluid via a heat exchanger 7 . Electricity will be produced from this heat, using a heating engine, without damaging the environment.…”
Section: Introductionmentioning
confidence: 99%
“…This heat can then be removed from the fluid via a heat exchanger. 7 Electricity will be produced from this heat, using a heating engine, without damaging the environment. The main factor affecting the system is the transfer of heat.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, optimization of the component parameters is highly essential and it involves time consumption and costlier experimentation, respectively. To overcome the above‐said difficulties in the optimization of the SWH units, various computational software and methods are developed to compute the effect of different performance parameters on the long‐term performance of the SWH system 6 …”
Section: Introductionmentioning
confidence: 99%